Identification of nonlinear dynamical systems from chaotic time series - Lu, Fangfang. (2008)
The thesis mainly focuses on the problem of nonlinear dynamical system identification from observed time series, which is one of the challenging topics in nonlinear time series analysis. The problem of nonlinear dynamical system identification is addressed in this thesis in three aspects: parameter identification; estimation of parameters and unobserved trajectory components; determination of the optimal model structure.